Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas V Tema 8 SDN Sungai Lulut 7 Banjarmasin - Sarina; Asrani (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem with this research is that learning is done by lecturing by the teacher, students' curiosity is still lacking, and students have not been optimally involved in Science material Theme 8 Our Friend's Environment using the Problem Based Learning, Mind Mapping, dan Course Review Horay models. The aim of the research was to describe teacher activities, and to analyze student activities and learning outcomes. Using a qualitative approach through instruments in the form of observation sheets of teacher and student activities and quantitatively using learning achievement tests. The results showed that teacher activity at meetings I-III always increased to obtain a score of 31 with the criteria of "Very Good". Student activity at meetings I-III always increases until it reaches the criterion "Almost all students are very active". Student learning outcomes at meetings I-III always increase to 100%.